DESAIN MULTIMEDIA INTERAKTIF BERBANTUAN LINKTREE PADA MATERI EKOSISTEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Imron Rosyadi; Sri Haryani; Sri Wardani; Wahyu Lestari; Noening Andrijati (STKIP Subang, 2024)
Elementary school children receive instruction in the field of science. When it comes to education, this particular subject matter is primarily conveyed through lectures, and students are instructed to commit the information to memory. Consequently, pupils often adopt a passive attitude and become easily bored if the teacher fails to provide any variations. Critical thinking skills refer to the cognitive abilities possessed by students in the 21st century to effectively address questions related to the reasons and methods behind certain phenomena. These skills enable students to arrive at logical conclusions based on principles and concepts. Practically, students exhibit reduced engagement in responding to inquiries and encounter challenges when articulating issues pertaining to science. In order to fully develop students' critical thinking abilities, particularly in the context of problem-solving in Science Literacy, there is still need for improvement. Hence, the incorporation of interactive multimedia learning aids is essential to facilitate the process of acquiring knowledge. Interactive multimedia refers to a cutting-edge educational tool designed to enhance critical thinking skills through teaching materials, assessment, and evaluation. One example of such interactive multimedia is Linktree, which is specifically designed to captivate students' attention and facilitate focused learning in the classroom.